PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE MENCARI PASANGAN UNTUK MENINGKATKAN MOTIVASI BELAJAR PADA PEMBELAJARAN TEMATIK SISWA KELAS I SD NEGERI 024 TARAI BANGUN KECAMATAN TAMBANG KABUPATEN KAMPAR - Nenny Nenny (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
This research was motivated by the low level of student motivation in the thematic learning of students of class I SDN 024Tarai Bangun. This study aims to improve students' learning motivation on thematic learning on the theme of my enthusiasmthrough the application of partner-type cooperative learning in grade 1 students of SDN 024 Tarai Bangun . The subjects ofthis study were all grade 1 students of SDN 024 Tarai Bangun totaling 22 people, in 2017. The form of this research wasclassroom action research. This research instrument consists of performance instruments and data collection instruments inthe form of observation sheets of teacher activities and student activities. Based on the results of the analysis and discussionas stated it can be concluded that with the implementation of cooperative learning model, the type of finding a partner canincrease the Motivation of Learning in thematic learning, the theme of my enthusiasm is Class I SDN 024 Tarai Bangun . Incycle I shows that student learning motivation is still relatively low with a score of 46 with an average percentage of 4indicators of learning motivation of 52.3%. whereas in the second cycle reached a score of 69 with very high criteria, with anaverage student learning motivation for learning motivation indicators (4 indicators) of 78.4%.